LED packaging material and preparation method thereof

The copper-containing composite powder is prepared by combining copper nitrate and polyvinyl alcohol, and the copper oxide glass powder is added, which solves the problems of high cost and poor performance of LED packaging materials, and achieves efficient and uniform thermal conductivity and mechanical properties, which is suitable for large-scale Large-scale production and improve the light efficiency of LEDs.

CN119264588APending Publication Date: 2025-01-07NANCHANG LIANGMING IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411418949.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing LED packaging materials are costly and have limited sources and complex preparation processes, resulting in low production efficiency and high cost. The uneven distribution of phosphor particle size leads to tone drift and poor optical performance, and limited improvement in thermal conductivity.

Method used

Copper nitrate solution and polyvinyl alcohol solution are mixed with polyvinyl alcohol solution to prepare polyvinyl alcohol composite powder, composite film is prepared by ultrasonic dispersion and heat treatment, diamond is replaced to reduce costs, and copper oxide glass powder is added to improve thermal conductivity and optical properties.

Benefits of technology

It significantly reduces production costs, simplifies the preparation process, improves the uniformity of thermal conductivity and mechanical properties, enhances the overall performance of the composite film, is suitable for large-scale production, and improves the light efficiency and optical performance of LEDs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an LED packaging material and a preparation method thereof, and relates to the technical field of packaging material preparation, and the preparation method comprises the following steps: S1, mixing and stirring a copper nitrate solution and a polyvinyl alcohol solution, uniformly dispersing, washing, drying, calcining the dried product in an H2 atmosphere for 3-4 hours, and crushing to obtain copper-containing polyvinyl alcohol composite powder; s2, adding copper-containing polyvinyl alcohol composite powder into a polyvinyl alcohol solution, stirring and mixing uniformly, performing ultrasonic dispersion to obtain a film solution, spreading the film solution onto a PET film, drying for 3-4 hours at 40-50 DEG C, and demolding from the PET film to obtain a composite film, namely the LED packaging material; the heat conductivity and the mechanical property of the LED packaging material can be improved, the refractive index and the light transmittance are remarkably improved, the process is simplified, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of packaging material preparation, and in particular to an LED packaging material and a preparation method thereof. Background Art

[0002] LED (semiconductor light emitting diode) packaging refers to the packaging of light-emitting chips, which is quite different from integrated circuit packaging. LED packaging not only requires protection of the wick, but also requires light transmission. Therefore, LED packaging has special requirements for packaging materials.

[0003] LED is composed of chip, metal wire, bracket, conductive glue, packaging material, etc. The packaging material mainly plays the role of sealing and protecting the normal operation of the chip to prevent it from being affected by humidity and temperature in the surrounding environment; fixing and supporting the wires to prevent electronic components from being damaged by mechanical vibration and impact, which may cause changes in component parameters; reducing the refractive index difference between the LED chip and the air to increase light output and effectively discharge the heat generated inside.

[0004] Phosphor materials are an important factor that restricts the performance of LEDs. Currently, phosphors used in LED packaging materials are mostly made by ball mills. This type of phosphor is easy to precipitate and settle from the fluorescent slurry during coating, resulting in uneven coating, which can easily lead to a shift in the color tone of white light and blue or yellow spots on the color of the light-emitting diode. In addition, since the particle size distribution of phosphors made by existing ball mills is relatively wide, the appearance is irregular and easy to aggregate, when preparing packaging materials, it is necessary to place the phosphors in a ball mill together with corundum grinding beads for at least 2 hours and dry them. Then, the dried composite powder needs to be screened, followed by high-temperature hot pressing, sintering and other treatments. Finally, the sintered body needs to be surface ground and polished before the preparation can be completed. For example, the Chinese invention patent application with Chinese patent application number CN20091015436.0 and application date November 30, 2009, entitled "A phosphor / glass composite for semiconductor lighting and its preparation method", uses the phosphor of this patent to prepare LED materials, but has the following main disadvantages: a ball mill is required, and the powder is mixed with corundum beads for ball milling, and the mixing time is too long; the dried composite powder needs to be sieved, and then surface grinding and polishing are required. The entire preparation process is complicated, inefficient, and costly.

[0005] In addition, in order to improve the thermal conductivity of polymer-based composite films, current research mainly focuses on adding thermal conductive particles to polymer films, including metal nanoparticles, metal oxides, metal nitrides, graphene and carbon nanotubes, etc. to improve their thermal conductivity. However, nanoparticles are easy to agglomerate, resulting in limited improvement in the thermal conductivity of the composite film. Chinese patent document CN201910370781.6 discloses a hydroxylated hexagonal boron nitride / polyvinyl alcohol / lignin nanoparticle thermal conductive composite film material and a preparation method thereof. Although the strength and thermal stability of the prepared composite film are improved to a certain extent, the thermal conductivity is not ideal.

[0006] The invention patent with Chinese patent announcement number CN202211545357.9 discloses an LED packaging material and a preparation method thereof. The invention first pre-treats the diamond, and under the action of the cross-linking agent epichlorohydrin, polyethyleneimine is grafted on the surface of the diamond, and then copper ions are loaded on the diamond through the chelation of amino groups, and then calcined in a hydrogen atmosphere to obtain modified diamond loaded with copper; the invention first performs surface modification on the diamond to improve the dispersion performance of the diamond in the polyvinyl alcohol aqueous solution, and then copper is loaded on the surface of the diamond through chelation and calcination, avoiding the problem of agglomeration caused by direct addition of copper powder, thereby enhancing the mechanical properties and thermal conductivity of the film. At the same time, the synergistic effect of copper and diamond is conducive to the transfer of heat in the film structure. In addition, the amino groups in the polyethyleneimine form hydrogen bonds with the hydroxyl groups in the polyvinyl alcohol, and the mechanical properties of the composite film are further improved through hydrogen bonding.

[0007] Although the above process enhances the mechanical properties and thermal conductivity of the film to a certain extent, diamond is a rare material with limited sources and high price, which significantly increases the cost of the entire packaging material and is not conducive to large-scale production. Summary of the invention

[0008] The embodiments of the present application provide an LED packaging material and a preparation method thereof, thereby solving the problem of expensive LED packaging materials and limited sources in the prior art, improving the thermal conductivity and mechanical properties of the LED packaging material, reducing production costs, and enabling large-scale production.

[0009] The present invention provides a method for preparing an LED packaging material, which specifically includes the following steps: S1, mixing the copper nitrate solution and the polyvinyl alcohol solution, stirring, washing and drying after being evenly dispersed, and then calcining the dried product in a hydrogen atmosphere for 3-4 hours, and crushing to obtain a polyvinyl alcohol composite powder containing copper; S2. Add the copper-containing polyvinyl alcohol composite powder to the polyvinyl alcohol solution, stir and mix evenly, and disperse by ultrasonic to obtain a film liquid. Spread the film liquid on a PET film, dry at 40-50°C for 3-4h, and then demould from the PET film to obtain a composite film, which is the LED packaging material.

[0010] Furthermore, in step S1, the mass fraction of the copper nitrate solution is 5-8%, the mass fraction of the polyvinyl alcohol solution is 5-10%, and the mass ratio of the copper nitrate solution to the polyvinyl alcohol solution is 1:(5-10).

[0011] Furthermore, in step S2, the mass ratio of the copper-containing polyvinyl alcohol composite powder to the polyvinyl alcohol solution is 1:(20-35), and the mass fraction of the polyvinyl alcohol solution is 9-10%.

[0012] Furthermore, the copper oxide glass powder is substituted for the copper-containing polyvinyl alcohol composite powder prepared in step S1.

[0013] Furthermore, the particle size of the copper oxide glass powder is 10-100 nm.

[0014] Furthermore, the mass fraction of copper oxide in the copper oxide glass powder is 2%-4%.

[0015] Furthermore, the mass ratio of the copper oxide glass powder to polyvinyl alcohol is 1:(20-35).

[0016] Furthermore, the copper oxide glass powder is subjected to a reduction reaction before being added into the polyvinyl alcohol solution.

[0017] Furthermore, the reduction reaction is specifically as follows: washing and drying the copper oxide glass powder, and then calcining it in a hydrogen atmosphere for 2-3 hours to obtain copper oxide glass loaded with copper.

[0018] An LED packaging material is prepared by the above preparation method.

[0019] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: Compared with diamond, polyvinyl alcohol as a carrier is cheap and easy to obtain. Using polyvinyl alcohol as an alternative material can significantly reduce production costs and achieve industrial large-scale production; The preparation process of this scheme is simple, and the copper-containing polyvinyl alcohol composite powder is prepared directly by mixing and stirring the copper nitrate solution and the polyvinyl alcohol solution, which reduces multiple modification and loading processes, thereby simplifying the overall preparation process, improving production efficiency, and reducing energy consumption and waste generation in the production process, thereby realizing industrial production. Copper is directly combined with the polyvinyl alcohol matrix, which enhances the interfacial compatibility between copper and polyvinyl alcohol. The copper-containing polyvinyl alcohol composite powder is easy to disperse in the polyvinyl alcohol solution. The powder is evenly distributed in the solution, which can improve the uniformity and consistency of the composite film, thereby improving the uniformity of the thermal conductivity and mechanical properties of the packaging material and enhancing the overall performance of the composite film. By adjusting the ratio of copper nitrate solution to polyvinyl alcohol solution, the ratio of polyvinyl alcohol composite powder containing copper to polyvinyl alcohol, and the placement position of the composite powder, the performance of the composite film can be adjusted, thereby improving the flexibility and controllability of the preparation process; The copper-containing polyvinyl alcohol composite powder is easy to disperse in the polyvinyl alcohol solution. The addition of copper improves the thermal conductivity of the material. Polyvinyl alcohol itself has good flexibility and impact resistance, which enhances the thermal conductivity and mechanical properties of the composite film. It can also significantly change the optical properties of the composite film, increase the refractive index to 1.6, and increase the transmittance by about 10%. By adjusting the powder content and particle size, the optical properties of the packaging material can be controlled to make it more suitable for LED packaging, improve the LED light efficiency, and simplify the preparation process.

[0020] See the table below for specific technical parameter comparison: Comparative performance This application CN20091015436.0 CN201910370781.6 CN202211545357.9 Refractive Index 1.6 <1.6 <1.6 <1.6 Thermal conductivity better generally Poor generally Preparation process Simplified and efficient Simpler complex complex cost Lowest cost Lower cost Cost is average High raw material cost, not conducive to large-scale production DETAILED DESCRIPTION

[0021] To facilitate understanding of the present invention, the present application will be described in more detail below; however, the present invention can be implemented in many different forms and is not limited to the embodiments described herein; on the contrary, these embodiments are provided for the purpose of providing a more thorough and comprehensive understanding of the disclosure of the present invention.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0023] Embodiment 1: The present application provides a method for preparing an LED packaging material, which specifically comprises the following steps: S1, mixing the copper nitrate solution and the polyvinyl alcohol solution, stirring, washing and drying after being evenly dispersed, and then calcining the dried product in a hydrogen atmosphere for 3-4 hours, and crushing to obtain a polyvinyl alcohol composite powder containing copper; The mass fraction of the copper nitrate solution is 5-8%, the mass fraction of the polyvinyl alcohol solution is 5-10%, and the mass ratio of the copper nitrate solution to the polyvinyl alcohol solution is 1: (5-10); S2, adding the copper-containing polyvinyl alcohol composite powder to the polyvinyl alcohol solution, stirring and mixing evenly, and ultrasonically dispersing to obtain a film liquid, spreading the film liquid on a PET film, drying at 40-50° C. for 3-4 hours, and then demolding from the PET film to obtain a composite film, which is an LED packaging material; The mass ratio of the copper-containing polyvinyl alcohol composite powder to the polyvinyl alcohol solution is 1:(20-35), and the mass fraction of the polyvinyl alcohol solution is 9-10%.

[0024] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Compared with diamond in the reference document, polyvinyl alcohol as a carrier is cheap and easy to obtain. Using polyvinyl alcohol as an alternative material can significantly reduce production costs and achieve industrial large-scale production; Compared with the multiple steps of diamond treatment and modification in the reference document, the preparation process of this solution is simple, and the copper-containing polyvinyl alcohol composite powder is prepared directly by mixing and stirring the copper nitrate solution and the polyvinyl alcohol solution, which reduces the multiple modification and loading processes in the reference document, thereby simplifying the overall preparation process, improving production efficiency, and reducing energy consumption and waste generation in the production process, and can realize industrial production; Copper is directly combined with the polyvinyl alcohol matrix, which enhances the interfacial compatibility between copper and polyvinyl alcohol. The copper-containing polyvinyl alcohol composite powder is easy to disperse in the polyvinyl alcohol solution. The powder is evenly distributed in the solution, which can improve the uniformity and consistency of the composite film, thereby improving the uniformity of the thermal conductivity and mechanical properties of the packaging material and enhancing the overall performance of the composite film. By adjusting the ratio of copper nitrate solution to polyvinyl alcohol solution, the ratio of polyvinyl alcohol composite powder containing copper to polyvinyl alcohol, and the placement position of the composite powder, the performance of the composite film can be adjusted, thereby improving the flexibility and controllability of the preparation process; The copper-containing polyvinyl alcohol composite powder is easily dispersed in the polyvinyl alcohol solution. The addition of copper improves the thermal conductivity of the material. Polyvinyl alcohol itself has good flexibility and impact resistance, which enhances the thermal conductivity and mechanical properties of the composite film and simplifies the preparation process.

[0025] Embodiment 2: Embodiment 1 above reduces the cost and simplifies the preparation process by replacing diamond with polyvinyl alcohol solution as a carrier. To further improve the performance of LED packaging materials, further optimization is made on the basis of Embodiment 1.

[0026] In step S2, copper oxide glass powder is substituted for the copper-containing polyvinyl alcohol composite powder prepared in step S1 and added to the polyvinyl alcohol solution; Specifically, copper oxide glass powder is added to polyvinyl alcohol solution, stirred and mixed evenly, and ultrasonically dispersed to obtain a film liquid, the film liquid is spread on a PET film, dried at 40-50° C. for 3-4 hours, and then demolded from the PET film to obtain a composite film, which is an LED packaging material; The particle size of the copper oxide glass powder is 10-100 nm, the mass fraction of copper oxide in the copper oxide glass powder is 2%-4%, and the mass ratio of the copper oxide glass powder to polyvinyl alcohol is 1: (20-35).

[0027] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The copper oxide component in the copper oxide glass powder has good thermal conductivity, which can improve the thermal conductivity of the composite film and enhance the service life and performance stability of the LED material; The addition of copper oxide glass powder can change the optical properties of the composite film, such as refractive index and transmittance. By adjusting the content and particle size of copper oxide glass powder, the optical properties of the packaging material can be controlled, making it more suitable for LED packaging and improving the light efficiency. Compared with first preparing the copper-containing polyvinyl alcohol composite powder, directly adding the copper oxide glass powder simplifies the production process, reduces the production steps and time cost, and improves the production efficiency; The glass component can enhance the hardness and wear resistance of the composite material, and the addition of copper oxide glass powder can improve the mechanical strength of the composite film, making the packaging material less likely to deform or be damaged when subjected to external forces, further improving the mechanical properties of the composite film; Copper oxide glass has high chemical stability and can maintain stable material performance under various environmental conditions, thereby extending the service life of the composite material and adapting to complex and changing working environments. Due to the addition of copper oxide glass powder, the thermal conductivity, mechanical strength and chemical stability of the composite material are improved, thereby expanding the application range of the material.

[0028] Embodiment 3: Embodiment 2 above improves the mechanical properties and thermal conductivity of the composite material by using copper oxide glass powder as a thermal conductive material. To further improve the performance of the LED packaging material, further optimization is performed on the basis of Embodiment 2.

[0029] The copper oxide glass powder in step S2 is also subjected to a reduction reaction before being added to the polyvinyl alcohol solution, as follows: The copper oxide glass powder is washed and dried, and then the dried product is calcined in a hydrogen atmosphere for 2-3 hours to obtain copper oxide glass loaded with copper.

[0030] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The copper oxide in the copper oxide glass powder has good thermal conductivity. By calcining in a hydrogen atmosphere, the copper ions are reduced to copper element, and copper is further loaded on the surface of the copper oxide glass to form a dual thermal conductivity mechanism and an effective thermal conduction network, which can significantly improve the efficiency and speed of heat conduction and further enhance the heat dissipation capacity of LED packaging materials. The copper loaded on the surface of the copper oxide glass powder can form a better thermal connection with the polyvinyl alcohol matrix. This improved interface heat transfer can improve the overall heat dissipation performance of the composite material, ensuring that the LED will not be degraded or damaged due to overheating during operation, thereby improving the stability of the LED. The loading of copper can enhance the chemical stability of copper oxide glass. The copper oxide glass loaded with copper has better dispersibility and can be evenly dispersed in the polyvinyl alcohol solution, avoiding agglomeration and forming a more homogeneous composite film, thereby improving the overall performance of the packaging material. By controlling the copper loading and the ratio of copper oxide glass, the properties of the composite membrane can be adjusted, improving the flexibility of the preparation process.

[0031] The comparative composite membrane was prepared by the method disclosed in CN115850751B, wherein nanodiamond was modified and the modified diamond was loaded with copper.

[0032] The films prepared in Examples 1 to 3 and the comparative example were subjected to performance tests, wherein the thermal conductivity test method was carried out in accordance with the standard of GB / T 10295-2008, and the tensile strength and elongation at break were tested in accordance with the standard of GB / T1040.3-2006. The test results are shown in the following table: Thermal conductivity (w / (m·k)) Tensile strength (MPa) Elongation at break (%) Embodiment 1 2.61 84.3 191 Embodiment 2 2.82 82.7 186 Embodiment 3 3.31 73.5 175 Comparative Example 2.83 68.2 166 The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an LED packaging material, characterized in that: The specific steps include: S1, mixing the copper nitrate solution and the polyvinyl alcohol solution, stirring, washing and drying after being evenly dispersed, and then calcining the dried product in a hydrogen atmosphere for 3-4 hours, and crushing to obtain a polyvinyl alcohol composite powder containing copper; S2. Add the copper-containing polyvinyl alcohol composite powder to the polyvinyl alcohol solution, stir and mix evenly, and disperse by ultrasonic to obtain a film liquid. Spread the film liquid on a PET film, dry at 40-50°C for 3-4h, and then demould from the PET film to obtain a composite film, which is the LED packaging material.

2. The method for preparing an LED packaging material according to claim 1, characterized in that: In step S1, the mass fraction of the copper nitrate solution is 5-8%, the mass fraction of the polyvinyl alcohol solution is 5-10%, and the mass ratio of the copper nitrate solution to the polyvinyl alcohol solution is 1:(5-10).

3. The method for preparing an LED packaging material according to claim 1, characterized in that: The mass ratio of the copper-containing polyvinyl alcohol composite powder to the polyvinyl alcohol solution in step S2 is 1:(20-35), and the mass fraction of the polyvinyl alcohol solution is 9-10%.

4. The method for preparing an LED packaging material according to claim 1, characterized in that: The copper oxide glass powder is substituted for the copper-containing polyvinyl alcohol composite powder prepared in step S1.

5. The method for preparing an LED packaging material according to claim 4, characterized in that: The particle size of the copper oxide glass powder is 10-100 nm.

6. The method for preparing an LED packaging material according to claim 4, characterized in that: The mass fraction of copper oxide in the copper oxide glass powder is 2%-4%.

7. The method for preparing an LED packaging material according to claim 4, characterized in that: The mass ratio of the copper oxide glass powder to polyvinyl alcohol is 1:(20-35).

8. The method for preparing an LED packaging material according to claim 4, characterized in that: The copper oxide glass powder is also subjected to a reduction reaction before being added into the polyvinyl alcohol solution.

9. The method for preparing an LED packaging material according to claim 8, characterized in that: The reduction reaction is specifically as follows: washing and drying the copper oxide glass powder, and then calcining it in a hydrogen atmosphere for 2-3 hours to obtain copper oxide glass loaded with copper.

10. An LED packaging material, characterized in that: The LED packaging material is prepared by the preparation method of the LED packaging material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A thermally conductive composite film material of hydroxylated hexagonal boron nitride / polyvinyl alcohol / lignin nanoparticles and its preparation method

    CN110105603B

  • An LED packaging material and its preparation method

    CN115850751B